Suicide and loss of meaning in modernity: the educational role of the school in the formation of life narratives - Arevalos, Dario Hernán (2025)
This article examines the relationship between suicide and the sociocultural construction of pain in modernity from a sociological and educational perspective. The study aims to understand suicide not as a strictly individual or pathological phenomenon, but as an expression of social suffering produced by inequality, community fragmentation, and the loss of meaning in contemporary societies. Methodologically, a qualitative theoretical-documentary study was conducted, grounded in a hermeneutic-critical approach. A corpus of secondary sources—books, peer-reviewed articles, doctoral theses, and institutional reports—was reviewed, integrating classical contributions (Durkheim, Marx, Halbwachs, and Elias) with recent research on youth, school affectivity, and education. The findings show that suicide represents a form of social pain linked to processes of anomie, precarization, and the weakening of affective ties, which shape vulnerable subjectivities and constrain the symbolic elaboration of suffering. The discussion argues that schools, as ethical and political institutions, can play a central role in reconstructing life meaning through practices of recognition, care, and pedagogical support, fostering the development of life narratives oriented toward belonging and hope. It is concluded that addressing youth suicide requires moving beyond individualizing interpretations and adopting socio-educational frameworks that strengthen community bonds, emotional justice, and meaning-making processes, positioning the school as a strategic space for humanization and support in times of crisis.